The Influence Of The Dimensions Of Quality Information On Buyer-Supplier Relationships: Analysis From The Supplier Firm's Perspectives - Ahmad, Badrul Nizar (2007)
This study introduces how information quality plays an important role in the supply chain management, particularly in the buyer supplier relationships. With the current trend of business competitiveness and robust changing environments, the ability for the companies to react fast will much depends on the quality of information that can be shared between the buyer and the supplier. This study is primarily undertaken to investigate what are the dimensions of information quality that are important in influencing the buyer-supplier relationships, and ultimately can increase firms' effectiveness in supply chain management.